Trigeminal neuralgia: a systematic review - Lima, Bruno José Santos (2021)
Paroxysmal attacks of excruciating pain characterize trigeminal neuralgia, a clinical manifestation of an affection of the maxillary branch. It is considered one of the most severe and unbearable pains described by medicine, and can even lead to suicide. There is great difficulty in carrying out controlled therapeutic work on trigeminal neuralgia, as the cases are infrequent and it is unacceptable not to treat the patient in a placebo group. For this reason, the work in question aims to carry out a systematic review of the reports and descriptions existing in scientific journals. The present study consisted of a systematic review of the literature, with synthesis and analysis of clinical findings and meta-analysis of the quantitative data available in articles from indexed journals, both in Brazil and in other countries. Trigeminal neuralgia is a condition with pathophysiological mechanisms not fully understood. Drug therapy is considered the first-line treatment for NT. The anticonvulsant carbamazepine has been used since 1960 for its effectiveness in approximately 60% to 80% of patients.